2015
DOI: 10.1177/0363546515570465
|View full text |Cite
|
Sign up to set email alerts
|

Distal Biceps Brachii Tendon Repairs

Abstract: Both the single-incision CB and double-incision BT techniques provided excellent clinical results. Complications were more common in the single-incision CB group and most commonly involved paresthesias of the superficial radial nerve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 19 publications
0
10
1
5
Order By: Relevance
“…Several series have correlated the use of a single incision with higher complication rates, while multiple other studies have contradicted these findings. 2,8,10,11,13,15 Close examination of studies by Grewal et al, 8 Cain et al, 2 and Shields et al 13 shows that higher reported total complication rates with a single incision can be largely attributed to sensory neuropathies. 6 The frequency of less common major complications, including posterior interosseous nerve (PIN) palsy, symptomatic heterotopic ossification (HO), and proximal radioulnar synostosis, is not well documented because of the small size of reported series.…”
mentioning
confidence: 99%
“…Several series have correlated the use of a single incision with higher complication rates, while multiple other studies have contradicted these findings. 2,8,10,11,13,15 Close examination of studies by Grewal et al, 8 Cain et al, 2 and Shields et al 13 shows that higher reported total complication rates with a single incision can be largely attributed to sensory neuropathies. 6 The frequency of less common major complications, including posterior interosseous nerve (PIN) palsy, symptomatic heterotopic ossification (HO), and proximal radioulnar synostosis, is not well documented because of the small size of reported series.…”
mentioning
confidence: 99%
“… 1 , 16 , 22 , 23 Cortical button fixation has been shown to outperform bone tunnels, intraosseous screws, and suture anchors in biomechanical studies. 7 , 12 , 16 , 19 As noted previously, the most common major complication following surgery is PIN palsy, and unicortical button fixation may have the advantage of avoiding inadvertent injury to the PIN. 13 While these biomechanical studies were most demonstrative of time-zero construct strength and stability, there is minimal evidence evaluating techniques under cyclic loading conditions.…”
Section: Discussionmentioning
confidence: 88%
“… 5 , 6 , 7 , 8 Complications associated with primary anatomic repair include heterotopic ossification, radioulnar synostosis or loss of forearm rotation, lateral antebrachial cutaneous nerve or posterior interosseous nerve (PIN) palsy, and bicipital tuberosity fracture. 4 , 9 , 10 , 11 , 12 In a recent systematic review evaluating complications following distal biceps tendon repair, the authors noted that the most common major complication was PIN palsy (1.6%), followed by re-rupture (1.4%) and symptomatic heterotopic ossification (0.3%). 13 Bain et al.…”
mentioning
confidence: 99%
“…26 Single-incision cortical button demonstrated more complications (30%) compared to double-incision bone tunnel suture fixation (4.8%), mostly consistent with permanent superficial radial nerve paresthesias. 27 Overall, both techniques provided good clinical results.…”
Section: Treatment Of Tendon Tearsmentioning
confidence: 84%